2008
DOI: 10.1164/rccm.200710-1606oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension and Cor Pulmonale during Severe Acute Chest Syndrome in Sickle Cell Disease

Abstract: Pulmonary pressures increase during severe acute chest syndrome, and pulmonary hypertension is associated with cardiac biomarker elevation and a higher risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 41 publications
(50 reference statements)
3
75
0
2
Order By: Relevance
“…Second, we included all ACS episodes during the study period as commonly performed in the ACS literature which is by nature a relapsing disease 5. 8 28 Because all episodes may not be considered as being independent of one another, we confirmed our findings by a sensitivity analysis restricted to the first ACS episode.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Second, we included all ACS episodes during the study period as commonly performed in the ACS literature which is by nature a relapsing disease 5. 8 28 Because all episodes may not be considered as being independent of one another, we confirmed our findings by a sensitivity analysis restricted to the first ACS episode.…”
Section: Discussionmentioning
confidence: 62%
“…Several of these mechanisms may act during ACS. In particular, SCD patients may be prone to heart dilatation either due to chronic heart disease27 or acute cor pulmonale during severe episodes of ACS 28. These patients may also exhibit abdominal compartment syndrome in relation to immobilisation and morphine use for pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…In larger cohorts of adult patients with ACS, the need for mechanical ventilation predicted hospital deaths and resource utilization. 11,34,35 Loss of lung aeration as assessed by the LU score may be useful for the early identification of patients at higher risk of poor outcome. Whether early implementation of a more aggressive treatment in such patients may alter ACS outcome needs further research.…”
Section: Discussionmentioning
confidence: 99%
“…10 In patients with persistent respiratory distress despite red-blood-cell transfusion or partial-exchange transfusion, noninvasive mechanical ventilation was started; orotracheal intubation and invasive ventilation were used in patients who failed noninvasive ventilation. 11 …”
Section: Methodsmentioning
confidence: 99%
“…Bernini et al found that dexamethasone (0.3 mg/kg every 12 h 9 4 doses) decreased the need for blood transfusion and opioids in children with ACS, but this beneficial effect was counterbalanced by a trend towards increased frequency of readmission [21]. Acute pulmonary hypertension and right ventricular failure are common features of severe ACS episodes and have been associated with increased mortality [22]. Many mechanisms may cause pulmonary hypertension during ACS, including thrombosis-related vaso-occlusion and hemolysis-related vasoconstriction [23][24][25].…”
Section: Discussionmentioning
confidence: 99%